Allocating Cash Savings and the Role of Information: Evidence from a Field Experiment in Uganda - Niklas Buehren (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Microfinance in general and microcredit programs in particular have attracted much attention among interest groups concerned with poverty eradication and are seen by many as highly promising means in order to alleviate poverty. More recently, the spotlight has turned increasingly on the development and promotion of microsaving devices and mechanisms suitable to the unbanked poor. Along these lines, the Saving Mobilization program implemented by BRAC in Uganda is an attempt to encourage a saving culture as well as overcoming barriers to make use of saving services at more formal financial institutions. Building on a randomized control trial, the aim of this study is to investigate the impact of this program on the saving behavior of participants. The intervention is successful in increasing the usage of semi-formal financial institutions on the extensive margin as well as to boost the amount held at these institutions. The total amount of savings, however, remains unaffected. Impact heterogeneity is important and the analysis shows that illiterate individuals as well as individuals having experienced theft in the recent past are more likely to respond to the program.
Keywords: D04; D14; G21; O16; 330; Microfinance; saving promotion; theft; literacy; Uganda